2011
DOI: 10.1088/1748-9326/6/2/024019
|View full text |Cite
|
Sign up to set email alerts
|

Important role of ammonia on haze formation in Shanghai

Abstract: A haze episode occurred on 12 September 2009 in Shanghai, when the mass ratio of PM 1.0 /PM 2.5 (PM: particulate matter) reached 0.8. A similar variation of hygroscopic growth factor distribution was observed for Aitken mode particles and accumulation mode particles, implying that the enhancement of fine particles was caused by local atmospheric processing. The hygroscopicity measurements in combination with chemical analysis provided strong support for the significant contribution of (NH 4 ) 2 SO 4 and NH 4 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 20 publications
1
105
0
Order By: Relevance
“…2), the stable synoptic conditions which favored accumulation of emitted pollutants and rapid formation of secondary species were essential to the formation of the severe PM 2.5 pollution . The high daily average relative humidity (58.3-81.0%) on these three days also favored secondary inorganic aerosol formation through hygroscopic growth of ambient particles and heterogeneous reactions of gaseous precursors (Ye et al, 2011). Concentrations of K + and Cl -, influenced by anthropogenic activities such as biomass burning (Cheng et al, 2014) and coal combustion (Evans et al, 2011), also showed obvious increases during the two episodes.…”
Section: Relationship Between Nh 3 and Nh 4 + During Typical Pm 25 Pmentioning
confidence: 87%
See 1 more Smart Citation
“…2), the stable synoptic conditions which favored accumulation of emitted pollutants and rapid formation of secondary species were essential to the formation of the severe PM 2.5 pollution . The high daily average relative humidity (58.3-81.0%) on these three days also favored secondary inorganic aerosol formation through hygroscopic growth of ambient particles and heterogeneous reactions of gaseous precursors (Ye et al, 2011). Concentrations of K + and Cl -, influenced by anthropogenic activities such as biomass burning (Cheng et al, 2014) and coal combustion (Evans et al, 2011), also showed obvious increases during the two episodes.…”
Section: Relationship Between Nh 3 and Nh 4 + During Typical Pm 25 Pmentioning
confidence: 87%
“…However, what concerned people more was the impact of atmospheric NH 3 on particulate pollution. Ye et al (2011) studied the haze formation in Shanghai and found that the NH 3 played a vital role in the enhancement of particulate sulfate and nitrate during the haze episode. Gong et al (2013) found that elevated NH 3 levels were synchronous with enhancements in NH 4 + and SO 4 2-around midday in Houston during summertime and suggested NH 3 likely influenced both mass and number concentrations of particles.…”
Section: Introductionmentioning
confidence: 99%
“…haze (Ye et al, 2011;Meng et al, 2014;Wei et al, 2015). Global ammonia emission has more than doubled since preindustrial times, mainly because of agricultural intensification (Galloway et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This event motivated the release of the Action Plan on Prevention and Control of Air Pollution with the goal of reducing PM 2.5 (particulate matter smaller than 2.5 µm in aerodynamic diameter) concentration by 15-25 % (2012) by 2017 in three major city clusters (http://english.mep.gov.cn/News_service/ infocus/201309/t20130924_260707.htm). In order to reduce the PM 2.5 concentration, extensive studies have been conducted to investigate the sources and formation mechanisms of haze pollution in recent years (Ye et al, 2011;Sun et al, 2016;Qiao et al, 2016;Hu et al, 2016;Li et al, 2016;Guo et al, 2014Guo et al, , 2013Zheng et al, 2015;Wang et al, 2016;Peng et al, 2016). However, the haze formation mechanisms and source appointment of fine particles remain uncertain.…”
Section: Introductionmentioning
confidence: 99%